Effective Curriculum Management in Islamic Primary Education: A Case Study of Integrated Islamic Schools - Nurfaisal Nurfaisal; Sunengko Sunengko; M.Fadhly Farhy Abbas (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates curriculum management at SDIT Fadhilah, an Integrated Islamic School in Pekanbaru, Indonesia. The focus lies on balancing national academic standards and Islamic educational values, a key issue in contemporary Islamic education. The aim is to explore how the school integrates these dual priorities to foster academic and spiritual development. A qualitative case study approach was employed, collecting data through interviews, observations, and document analysis. The research addressed the question: How does SDIT Fadhilah implement, organize, and evaluate an integrated curriculum to achieve its dual educational goals?. Findings indicate that SDIT Fadhilah effectively integrates academic and religious education. However, significant challenges include inadequate instructional time for covering both curricula and the lack of standardized tools for assessing students' spiritual development. These issues hinder the coherence and quality of the integrated curriculum. To mitigate these challenges, the study recommends structured scheduling strategies, such as block scheduling or thematic units, to optimize instructional time. Additionally, it suggests developing standardized assessment tools, such as rubrics for character development and self-assessment journals for spiritual reflection, to ensure consistency in evaluating students' progress. These findings have broader implications for other Integrated Islamic Schools, underscoring the importance of strategic time management and assessment standardization in achieving holistic educational outcomes. Future research should conduct comparative studies across various schools to examine the broader applicability and long-term effects of these strategies, aiming to enhance curriculum management in Islamic education contexts.